Five new species of Coccothrinax (Cryosophileae, Coryphoideae, Arecaceae) from Hispaniola - Henderson, Andrew; Fernández, Eladio; Montero, Oscar; Clase, Teodoro; Gratacos, Xavier; Bacon, Christine D. (Phytotaxa, 2023)
Five new species of Coccothrinax from Hispaniola are described and illustrated. A key is given to all species from the island.